DOWEX...in a Modern Water Softener Gives You Rain-Soft Water Right Out of the Faucet! - Dow Chemical Company (1954)
Black and white print advertisement for Dowex, a high-capacity resin manufactured and sold by the Dow Chemical Company for use in water softeners. This advertisement appeared on page 77 of the September 11, 1954 edition of The Saturday Evening Post.
Keywords: Chemical industry; Dow Chemical Company; Water--Softening; Corporations; Water--Softening--Equipment and supplies; Women in advertising